On the spectral expansions connected with Schrödinger’s operator of continuous functions in a closed domain - Rakhimov, Abdumalik A.; Zakariya, Kamran; Ali Khan, Nazir (Lifescience Global, 2012)
Present paper is devoted to study of uniformly convergence of spectral expansions in a closed domain. We consider here as a spectral expansions eigenfunction expansions connected with one Schrodinger’s operator with singular potential in two dimensional domains with smooth boundary.